2016
DOI: 10.12816/0028282
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Succession Planning for Business Survival : A Case of Kwalita Business Consultants , Johannesburg ( South Africa )

Abstract: Succession planning is a subject that is not widely discussed in many organizations because of its sensitivity. Ignoring open discussions has been one of the biggest challenges facing contemporary organizations such as Kwalita Business Consultants. This study investigated succession planning practices at Kwalita Business Consultants. The significance of the study was that Kwalita Business Consultants management and employees were not aware of the importance of succession planning. This created awareness and mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 0 publications
2
4
0
Order By: Relevance
“…It indicates that succession planning has a positive impact on return on assets. This finding is consistent with the findings of Lowan and Chisoro (2016). Similarly, the beta coefficients for training and development is positive with return on assets.…”
Section: Regression Analysissupporting
confidence: 91%
See 2 more Smart Citations
“…It indicates that succession planning has a positive impact on return on assets. This finding is consistent with the findings of Lowan and Chisoro (2016). Similarly, the beta coefficients for training and development is positive with return on assets.…”
Section: Regression Analysissupporting
confidence: 91%
“…Prestera (2014) observed that succession planning offers a long-term commitment to workers by creating a firm's culture. Lowan and Chisoro (2016) revealed a positive relationship between job rotation and profitability of the banks. Likewise, Holbeche (2012) revealed a positive relationship between organization culture and profitability of the banks.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…The coefficient outcomes provided in Table 15 has shown that human resource strategy has a significant influence towards succession planning of the Kenyan state corporations in that, a unit change in human resource strategy tends to improve the process of succession planning by a margin of 62% given a coefficient value of .620 (t = 9.036, p = .000) The construct of human resource strategy has revealed a significant influence towards succession planning individually. The findings are in support of that of Lowan and Chisoro (2016) whose study revealed that succession planning helps individuals realize their career plans within the organization improves employee morale and their ability to respond to changing environmental demands as well as aiding with downsizing.…”
Section: Succession Planning and Human Resource Strategysupporting
confidence: 83%
“…This has endangered the efforts and spirit of succession planning in the organisations within the country (Yanney, 2017). Lowan and Chisoro (2016) further observed that one of the major drawbacks in establishing a succession plan in developing countries is the lack of support from top company executives. Citing the example of corporate politics, Lowan and Chisoro (2016) indicating that instead of supporting a system approach to succession planning using career development opportunities, top managers rather use the corporate ladder to promote friends and allies, while punishing enemies, regardless of talent or qualifications.…”
Section: Introductionmentioning
confidence: 99%